How to Implement SME Empowerment during the Covid-19 Pandemic? - Widjanarko, Hendro; Suratna, Suratna; Utomo, Humam Santosa; Wibawa, Tri (RSF Conference Series: Business, Management and Social Sciences, 2021)
The potential of Gunung Kidul beach tourism is getting bigger with the opening of highway access along the south coast. The existence of this potential is an opportunity for MSMEs in coastal areas to improve community welfare. The author has found a formulation of the SME development strategy based on the results of previous studies with the Gunung Kidul Regional Government and SMEs in the south coast area. The implementation of the partnership strategy has been implemented by the Regional Government, although it is still in the early stages of implementation. This paper reviews the implementation of the SME development strategy during the pandemic implemented by the Gunung Kidul Regional Government. The analytical method used in the research is a qualitative and quantitative analysis by developing various sources of information through focus group discussions, interviews, observations, policy studies, as well as a study of secondary data on SMEs and tourism in Gunung Kidul Regency. SMEs involved in this study consisted of clusters selling fresh fish and culinary delights. The results of the study reveal that strategic issues that have occurred during the pandemic have a negative impact on SMEs. The strategy for empowering SMEs needs to be made several adjustments according to the internal conditions of SMEs and pandemic conditions.